"Nothing Is Imposed in This Policy!": The Construction and Constriction of the European Neighbourhood. (November 2014) - Horký-Hlucháň, Ondřej; Kratochvíl, Petr
The article argues that postcolonial, postdevelopment, Balkanist and East–West slope theories, which reflect the asymmetric relations between "Europe" and its former colonies or other regions on the periphery of the continent, are most likely to give an accurate analysis of the mechanism of the European Neighborhood Policy (ENP). We offer a new conceptualization of the European Neighborhood and suggest that the European Union (EU) constructs its neighborhood as an ambiguous and transitional other while masking the asymmetric and dominant structure of the ENP through a liberal-democratic discourse. A critical discourse analysis of official documents and speeches confirms the ambiguity, transitiveness, and concealed dominance of the policy and the not-so-benign normative character of the EU. It also suggests that the neighborhood of Europe is not a fixed place and its continuous recreation helps the core of Europe to control the regions and make them comply with its normative as well as geographic expansion. In this respect, the ENP shows striking similarities with policies of colonialism and neocolonialism.